الأداء الوظيفي وعلاقته بالتدين - طعام,عمر (University of Eloued جامعة الوادي, 2024)
من خلال المقال المعنون بالأداء الوظيفي وعلاقته بالتدين وهو عبارة عن دراسة ميدانية على عينة من عمال شركة توزيع الكهرباء والغاز للغرب ببشار حيث وبعد التقديم للموضوع تم تقسيم الدراسة الى ثلاثة أجزاء بدايتها تم طرح الإشكالية الرئيسية والتي مفادها: ما علاقة الأداء الوظيفي بالتدين لدى العمال في شركة توزيع الكهرباء والغاز من وجهة نظر (أعوان التحكم)؟ وبعد تحديد المفاهيم الاساسية للدراسة والمتمثلة في الاداء الوظيفي والتدين تمت الاشارة الى اهم الدراسات السابقة للموضوع، تم طرح الافتراض الرئيسي والذي مفاده: كلما زاد التدين ارتفع الاداء الوظيفي للعمال داخل مؤسسة سونلغاز. وقد شملت العينة 60 مبحوثا ووصفت العينة بالمسح الشامل، وتم تطبيق اداة الاستمارة من اجل جمع المؤشرات المتعلقة بالبحث، بما في ذلك تطبيق مقياس التدين على عينة البحث. وفي نهاية الدراسة تم التوصل الى نتائج وهي: كلما ارتفع التدين زاد الاداء الوظيفي لدى عينة الدراسة، ومن النتائج المحصل عليها ايضا يعمل التدين على تجاوز ضغوطات العمل.Abstract: Enter Through the article entitled Job performance and its relationship to religiosity, which is a field study on a sample of workers from the Western Electricity and Gas Distribution Company in Bechar. After introducing the topic, the study was divided into three parts. At the beginning, the main problem was raised, which is: What is the relationship between job performance and religiosity among workers in the Distribution of electricity and gas from the point of view of (control agents)? And after defining the basic concepts of the study, namely job performance and religiosity, reference was made to the most important previous studies on the subject. The main assumption was put forward, which states: The greater the religiosity, the higher the job performance of workers within the Sonelgaz Foundation. The sample included 60 respondents, and the sample was described as a comprehensive survey. The questionnaire tool was applied to collect indicators related to the research, including applying a measure of religiosity to the research sample. At the end of the study, results were reached as the higher the religiosity, the higher the job performance among the study sample. Among the results obtained, religiosity works to overcome work pressures.
دراسة ميدانية على عمال أعوان التحكم بشركة توزيع الكهرباء والغاز للغرب بشار
Keywords: التدين; الأداء: religiosity; Functionality; Work